A comprehensive, cell specific microRNA catalogue of human peripheral blood. Issue 16 (11th August 2017) - Juzenas, Simonas; Venkatesh, Geetha; Hübenthal, Matthias; Hoeppner, Marc P.; Du, Zhipei Gracie; Paulsen, Maren; Rosenstiel, Philip; Senger, Philipp; Hofmann-Apitius, Martin; Keller, Andreas; Kupcinskas, Limas; Franke, Andre; et al.
Abstract: With this study, we provide a comprehensive reference dataset of detailed miRNA expression profiles from seven types of human peripheral blood cells (NK cells, B lymphocytes, cytotoxic T lymphocytes, T helper cells, monocytes, neutrophils and erythrocytes), serum, exosomes and whole blood. The peripheral blood cells from buffy coats were typed and sorted using FACS/MACS. The overall dataset was generated from 450 small RNA libraries using high-throughput sequencing. By employing a comprehensive bioinformatics and statistical analysis, we show that 3′ trimming modifications as well as composition of 3′ added non-templated nucleotides are distributed in a lineage-specific manner—the closer the hematopoietic progenitors are, the higher their similarities in sequence variation of the 3′ end. Furthermore, we define the blood cell-specific miRNA and isomiR expression patterns and identify novel cell type specific miRNA candidates. The study provides the most comprehensive contribution to date towards a complete miRNA catalogue of human peripheral blood, which can be used as a reference for future studies. The dataset has been deposited in GEO and also can be explored interactively following this link: http://134.245.63.235/ikmb-tools/bloodmiRs .